BIQUAD ANTENNA DESIGN WITH CIRCLE REFLECTORS - Pratama, Nanta Aprilian; Marpaung, Jannus; Suryadi, Dedy (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
This research is about how to develop a signal receiving antenna using cans as a reflector and copper wire in the form of BiQuad as a drive. With the experimental method directly to the research site which is useful for analyzing each captured signal strength. One of the objectives of this research is to support the improvement of the creative economy in Sungai Kupah Village, where the area really needs help from signal strength. The results of this study indicate that using only a can antenna can improve the GSM signal quality. There are 2 providers used, namely Tri and Telkomsel by taking variable values from Signal Strength, RSSI, SINR, RSRP, RSRQ, Ping, Upload, Download and taking the daily data for 5 research days in the morning and evening which aims to analyze any change in the value of the variable data. The average value obtained by the Tri provider for 5 days in the morning at Signal Strength -113.4 dBm, RSSI -82.64 dBm, SINR 4.78 dB, RSRP -113.4 dBm, RSRQ -13.2 dB , Ping 168.21 ms, Upload 37.68 Mbps, Download 2.08 Mbps. The average value obtained by the Tri provider for 5 days in the afternoon at Signal Strength -112.8 dBm, RSSI -82.36 dBm, SINR 4.56 dB, RSRP -112.8 dBm, RSRQ 13.3 dB, Ping 194.60 ms, Upload 20.52 Mbps, Download 9.15 Mbps. The average Telkomsel provider gets for 5 days in the morning at Signal Strength -115.8 dBm, RSSI -87.16 dBm, SINR 4.56 dB, RSRP -115.8 dBm, RSRQ -10.3 dB, Ping 189.14 ms, Upload 23.52 Mbps, Download 15.67 Mbps. The average Telkomsel provider gets for 5 days in the afternoon at Signal Strength -113.8 dBm, RSSI -86.12 dBm, SINR 6.16 dB, RSRP -113.8 dBm, RSRQ -9.7 dB, Ping 157.52 ms, Upload 31.83 Mbps, Download 22.27 Mbps.